How Does Dualistic Passion Fuel Academic Thriving? A Joint Moderated–Mediating Model - Zhou, Jie (Frontiers in Psychology, 2021)
Based on the dualistic model of passion, this study developed a joint moderated mediating model to investigate the mechanism of dualistic passion on academic thriving. We surveyed 960 Chinese university students with questionnaire. The results showed that harmonious and obsessive passion positively predicted academic thriving, with the effect of harmonious passion being stronger. Academic personal best goal mediated these relationships. Moreover, threat stress appraisal and academic workload jointly moderated the relationships of harmonious and obsessive passion with academic personal best goal, respectively, and the first stage of the mediating effect of academic personal best goal between harmonious and obsessive passion and academic thriving. Specifically, for low threat stress appraisal and academic workload, the direct effect of harmonious passion on academic personal best goal and the mediating effect of academic personal best goal were stronger. Meanwhile, for high threat stress appraisal and academic workload, the same applied for obsessive passion. These findings provide important implications for educational practice by highlighting an underlying mechanism of how and when dualistic passion, particular for obsessive passion, can initiate and maintain academic thriving.